Anti-inflammatory effect of the flavonoid fraction of Lepechinia meyenii (Walp.) Epling (Sage) on leukocytes of patients with rheumatoid arthritis - Carlos Alberto Arenas-Chavez; Tomas Wiche-Salinas; Ignacio Valencia-Mercado; Ronald Calle-Valdez; Corina Vera-Gonzales; Stephanie Malaga-Contreras; Fernando Flores-Rivera; Carlos Huanqui-Guerra (Revista Peruana de Medicina Experimental y Salud Pública, 2018)
Objectives. to assess the anti-inflammatory effect of the flavonoid fraction of Lepechinia meyenii (Walp.) Epling on leukocytes of patients with rheumatoid arthritis (RA). Materials and Methods. Plants of the species Lepechinia meyenii (Walp.) Epling were collected and then different flavonoid fractions were extracted by column and thin layer chromatography. The superoxide anion production was evaluated by means of the reduction of nitroblue tetrazolium assay technique in neutrophils obtained from the blood of patients with RA, divided into three groups: negative control, which consisted of neutrophils (5x105 cells); positive control, made up of PMA (phorbol myristate acetate)-activated neutrophils (150 ng/mL), and the treatments, comprised of neutrophils activated and treated with different concentrations of the flavonoid fraction LM8 (60, 120, and 180 ug/mL). The expression of proinflammatory genes was studied by RTqPCR in mononuclear leukocytes obtained from patients with RA, divided into three groups: negative control, which consisted of mononuclear leukocytes (5x105 cells); positive control, made up of phytohaemagglutinin (PHA) (150 ug/ml)-activated mononuclear leukocytes, and the treatment, comprised of mononuclear leukocytes activated and treated with the flavonoid fraction LM8 (120 ug/mL). Results. Several flavonoid fractions were purified, with fraction LM8 showing the best immunomodulating effect. Said fraction diminished the superoxide anion production dependent on concentration. On the other hand, it diminished the expression of TNFα, IL8, and IL17 in mononuclear leukocytes. Conclusions. These results are encouraging in terms of the immunomodulating effect of this Peruvian medicinal plant and justify the continuation of their study for a potential clinical application.